The influence of V addition on the structure, mechanical properties, and oxidation behaviour of TiAlSiN coatings deposited by DC magnetron sputtering - AL-Rjoub, A. (2022)
The influence of V content on the morphology, structure, hardness (H) and reduced Young's modulus (E), adhesion, and oxidation resistance of TiAlSiN coatings is investigated. The coatings were produced by DC reactive magnetron sputtering, with increasing V contents from 0, 4.8 and 11.0 at.%. All coatings exhibit a fcc type structure. The coating with 4.8 at.% of V shows the highest values of H and E, whereas the values are similar for the reference coating and the coating with 11.0 at.% of V. The coatings adhere well to the substrates and show a dense and compact columnar growth extending from the adhesive interlayer to the top surface of the coatings. The dynamic thermal gravimetric oxidation curves reveal that V additions decreases the onset point of oxidation significantly and degrades the oxidation resistance of the coatings. A dual oxide layer is formed on the top surface of the reference coating: an outer porous Ti–Al–O rich layer with plate-like features on the top, which classified to TiO2 (rutile and anatase) and Al2O3 phases, and an inner Ti–Si–O rich layer with Al depletion that identified as mixture of amorphous Si–O and Ti–Si–O protective oxides. The diffusion of V to the top surface governs the oxidation process of the V-containing coatings, i.e. increasing V concentration leads to disrupt the formation of the protective continuous oxide layers easily.